STRATEGI PERAN VARIASI PRODUK, CONTENT MARKETING DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINTIFIC PADA APLIKASI TIKTOK (STUDY KASUS PADA PENGGUNA TIKTOK DI KOTA BANDUNG) - Hadiansyah, Ari; Roisah, Riris (Jurnal Ekonomi Manajemen, 2025)
This study aims to examine the influence of Product Variation, Content Marketing, and Online Customer Reviews on Purchase Decisions of Skintific products via the TikTok application in Bandung. A quantitative approach was used, with primary data collected through questionnaires distributed to 98 respondents who are Skintific users and TikTok users residing in Bandung. The sampling technique applied was non-probability sampling, specifically purposive sampling. Data were analyzed using multiple linear regression with SPSS for Windows version 25. The results show that Content Marketing has a positive and significant influence on purchase decisions, both partially and simultaneously. This indicates that the more attractive and consistent the content marketing is, the higher the likelihood of consumer purchase decisions. Meanwhile, Product Variation and Online Customer Reviews do not show a positive and significant influence when tested partially. These findings suggest that Skintific needs to evaluate its product variation and customer reviews in order to enhance their impact on consumer purchasing decisions in the future.